Pengaruh Informasi Akuntansi dan Non Akuntansi Terhadap Underpricing Saham di BEI Periode 2018-2020 (Studi Kasus Perusahaan yang Melakukan IPO di Bursa Efek Indonesia (BEI) periode 2019-2021) - Ayu Maha Cahyaning Rum Azizih; Maslichah Maslichah; Abdul Wahid Mahsuni (Universitas Islam Malang, 2023)
This study aims to determine the effect of accounting and non-accounting information on stock underpricing on the IDX for the 2018-2020 period. The population in this study were all companies that made an initial public offering (IPO) in 2018 – 2020. The sampling technique was carried out by purposive sampling. The analysis comes using multiple linear regression. The results of this study indicate that simultaneously underwriter variables, firm age, inflation, ROA, DER, firm size and EPS have a significant effect on underpricing variables. Partially, the underwriter has a significant positive effect on underpricing. Partially, firm age has a significant negative effect on underpricing. Partially, inflation has a significant negative effect on underpricing. Partially, return on assets has a significant negative effect on underpricing. Partially, the debt to equity ratio has a significant negative effect on underpricing. Partially, firm size has a significant positive effect on underpricing. Partially Earning per share has no effect on underpricing. Keywords: Underwriter accounting information, company age, inflation, roa, der, company size, earning per share, underpricing.